Cyclic Behavior and Seismic Design of Bolted Flange Plate Steel Moment Connections - Sato, Atsushi; Newell, James D.; Uang, Chia-Ming (Engineering Journal, 2008)
The AISC Connection Prequalification Review Panel (CPRP) is currently reviewing the bolted flange plate moment connection for inclusion in the next edition of the AISC Prequalified Connections for Special and Intermediate Steel Moment Frames for Seismic Applications. To expand the experimental database for prequalifying the bolted flange plate (BFP) moment connection for special moment frames, cyclic testing of three full-scale BFP steel moment connection specimens has been conducted. Beam sizes for these specimens (W30x108, W30x148, and W36x50) were larger than previously tested to extend the range of available experimental results. All three specimens performed well and met the Acceptance Criteria of the AISC Seismic Provisions. The specimens achieved an interstory drift angle of 0.06 radians before failure.